Interactive Gait & Balance Training Module - Jorge Ruiz; Lisa J. Granville; Vicky Ribera; Tara Kai; Michael Smith; Maria van Zuilen; Bernard A. Roos (Association of American Medical Colleges, 2006)
Abstract Introduction The Interactive Gait and Balance Training Module is based on the fall risk assessment tool developed by M. Tinetti. This tool can be used to asses fall risk in a wide variety of settings including outpatient, acute, home, and long term care. Methods The computer-based training module was created as a reusable learning object, and is available in CD-ROM and web-based versions. In order to provide a complete experience and achieve the specified learning objectives, educators should use this tool in conjunction with preceptor-assisted instructional activities such as lectures, workshops, or small group discussions as part of a blended learning strategy. Results Satisfaction surveys and usability testing with 26 second-year medical students at the University of Miami Leonard M. Miller School of Medicine resulted in high usability satisfaction ratings. Discussion It was learned that design and development of this e-learning product was worthwhile despite the significant amount of time and resources devoted to it. The benefits have been significant in terms of reusability, access, and consistency. In fact, fellows and medical students from preclinical as well as clinical years have been able to reuse the resource as part of diverse instructional activities.